MODEL PENINGKATAN KINERJA KARYAWAN MELALUI ENTREPRENEURIAL LEADERSHIP DAN MOTIVASI KERJA DI INDUSTRI FINANCE PADA KSP KOPDIT TIMAU INDAH - Roby Yusuf Bekuliu; Anderiaz Zacharias; Yohannes Letu Hayon; Stefanus Oskar Avena Manehat; Lorensou Hendry Lucky Mae (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Timor, 2026)
This study aims to analyze a model for improving employee performance through Entrepreneurial Leadership and Work Motivation at KSP Kopdit Timau Indah. The research employed a quantitative approach using a survey method involving 68 respondents consisting of employees and operational staff of the cooperative. Data analysis techniques included descriptive statistics, validity testing, reliability testing, classical assumption testing, multiple linear regression analysis, t-test, F-test, and coefficient of determination analysis using SPSS version 26. The results indicate that Entrepreneurial Leadership has a positive and significant effect on Employee Performance, with a calculated t-value of 3.842 and a significance level of 0.000 < 0.05. Work Motivation also has a positive and significant effect on Employee Performance, with a calculated t-value of 4.917 and a significance level of 0.000 < 0.05. Simultaneously, Entrepreneurial Leadership and Work Motivation have a significant effect on Employee Performance, as evidenced by an F-value of 39.621 and a significance level of 0.000 < 0.05. The Adjusted R Square value of 0.548 indicates that 54.8% of the variation in Employee Performance can be explained by Entrepreneurial Leadership and Work Motivation, while the remaining 45.2% is influenced by other variables outside the scope of this study. The findings suggest that the implementation of innovative entrepreneurial leadership and the enhancement of work motivation can improve service quality and employee productivity within the cooperative.